Children of Eden : a novel - Graceffa, Joey, 1991-; Sullivan, Laura L., 1974- (New York : Keyword Press/Atria, 2016)
"Rowan is a second child in a world where population control measures make her an outlaw, marked for death. She can never go to school, make friends, or get the eye implants that will mark her as a true member of Eden. Indeed, her kaleidoscopic eyes may very well give her away to the ruthless Center government. Outside of Eden, Earth is poisoned and dead. All animals and most plants have been destroyed by a man-made catastrophe. Long ago, the brilliant scientist Aaron Al-Baz saved a pocket of civilization by designing the EcoPanopticon, a massive computer program that hijacked all global technology and put it to use preserving the last vestiges of mankind. Humans will wait for thousands of years in Eden until the EcoPan heals the world"--
Keywords: Population -- Juvenile fiction; Outlaws -- Juvenile fiction; Eden -- Juvenile fiction; Teenage girls -- Juvenile fiction; Population -- Fiction; Outlaws -- Fiction; Eden -- Fiction; Teenage girls -- Fiction; Dystopian fiction; Apocalyptic fiction; Science fiction; Dystopian fiction; Apocalyptic fiction; Science fiction